Upaya melatih pemahaman konsep fisika peserta didik melalui bahan ajar e-lkpd berbasis model BOPPPS - Rukmansyah, Dea Fibriani; Saregar, Antomi; Mustari, Mukarramah (Papanda Publisher, 2025)
This research is based on students low understanding of physics concepts due to learning that is still teacher-centered and the use of printed student worksheets that are not interactive enough. This research aims to develop an E-LKPD (Student Worksheet) based on the BOPPPS model (Bridge-in, Objective, Pre-assessment, Participatory Learning, Post-assessment, and Summary) as physics teaching material to train the conceptual understanding of eleventh-grade students. The method used is research and development, referring to the steps of the Borg & Gall model up to stage 9, which is product revision after usage testing, due to time limitations in the research. The development of E-LKPD based on the BOPPPS learning model yielded results from content experts indicating a very feasible category, while media experts categorized it as feasible. Limited trials with students were categorized as very feasible, and the results of usage tests with 100 students in three high schools in Bandar Lampung were categorized as very feasible. The response from physics educators also supports the feasibility of the E-LKPD, with a very feasible category. This research contributes to the use of technology. It is also innovative because it develops E-LKPD based on the BOPPPS model, which is relevant to the demands of 21st-century learning. It uses a systematic and structured learning model, enabling active student engagement, and has an attractive and easy-to-use product design with digital QR code technology. However, this research is still limited to three schools with a relatively small number of participants and has not quantitatively measured the improvement in learning outcomes.